XANAP: A real‐world, prospective, observational study of patients treated with rivaroxaban for stroke prevention in atrial fibrillation in Asia. Issue 4 (6th July 2018) - Kim, Young‐Hoon; Shim, Jaemin; Tsai, Chia‐Ti; Wang, Chun‐Chieh; Vilela, Gilbert; Muengtaweepongsa, Sombat; Kurniawan, Mohammad; Maskon, Oteh; Li Fern, Hsu; Nguyen, Thang Huy; Thanachartwet, Thititat; Sim, Kenneth; et al.
Abstract: Background: ROCKET AF and its East Asian subanalysis demonstrated that rivaroxaban was non‐inferior to warfarin for stroke/systemic embolism (SE) prevention in patients with non‐valvular atrial fibrillation (NVAF), with a favorable benefit–risk profile. XANAP investigated the safety and effectiveness of rivaroxaban in routine care in Asia‐Pacific. Methods: XANAP was a prospective, real‐world, observational study in patients with NVAF newly starting rivaroxaban. Patients were followed at ~3‐month intervals for 1 year, or for ≥30 days after permanent discontinuation. Primary outcomes were major bleeding events, adverse events (AEs), serious AEs and all‐cause mortality; secondary outcomes included stroke/SE. Major outcomes were adjudicated centrally. Results: XANAP enrolled 2273 patients from 10 countries: mean age was 70.5 years and 58.1% were male. 49.8% of patients received rivaroxaban 20 mg once daily (od), 43.8% 15 mg od and 5.9% 10 mg od. Mean treatment duration was 296 days, and 72.8% of patients had received prior anticoagulation therapy. Co‐morbidities included heart failure (20.1%), hypertension (73.6%), diabetes mellitus (26.6%), prior stroke/non‐central nervous system SE/transient ischemic attack (32.8%) and myocardial infarction (3.8%). Mean CHADS2, CHA2 DS2 ‐VASc and HAS‐BLED scores were 2.3, 3.7 and 2.1, respectively. The rates (events/100 patient‐years [95% confidence interval]) of treatment‐emergent major bleeding, stroke and all‐cause mortality were 1.5 (1.0‐2.1), 1.7 (1.2‐2.5) and 2.0 (1.4‐2.7), respectively. Persistence was 66.2% at the study end. Conclusions: The real‐world XANAP study demonstrated low rates of stroke and bleeding in rivaroxaban‐treated patients with NVAF from Asia‐Pacific. The results were consistent with the real‐world XANTUS study and ROCKET AF.